A model to predict the thermodynamic stability of abiotic methane-hydrogen binary hydrates in a marine serpentinization environment - Zhu, Zhiwei; Cao, Yuncheng; Zheng, Zihan; Wu, Nengyou; Chen, Duofu (Frontiers in Marine Science, 2023)
Abiotic methane (CH4) and hydrogen (H2), which are produced during marine serpentinization, provide abundant gas source for hydrate formation on ocean floor. However, previous models of CH4-H2 hydrate formation have generally focused on pure water environments and have not considered the effects of salinity. In this study, the van der Waals-Platteeuw model, which considered the effects of salinity on the chemical potentials of CH4, H2, and H2O, was applied in a marine serpentinization environment. The model uses an empirical formula and the Peng-Robinson equation of state to calculate the Langmuir constants and fugacity values, respectively, of CH4 and H2, and it uses the Pitzer model to calculate the activity coefficients of H2O in the CH4-H2-seawater system. The three-phase equilibrium temperature and pressure predicted by the model for CH4-H2 hydrates in pure water demonstrated good agreement with experimental data. The model was then used to predict the three-phase equilibrium temperature and pressure for CH4-H2 hydrates in a NaCl solutions, for which relevant experimental data are lacking. Thus, this study provides a theoretical basis for gas hydrate research and investigation in areas with marine serpentinization.